2010
DOI: 10.1172/jci42868
|View full text |Cite
|
Sign up to set email alerts
|

Anaplasma phagocytophilum induces Ixodes scapularis ticks to express an antifreeze glycoprotein gene that enhances their survival in the cold

Abstract: In the United States, Ixodes scapularis ticks overwinter in the Northeast and Upper Midwest and transmit the agent of human granulocytic anaplasmosis, Anaplasma phagocytophilum, among other pathogens. We now show that the presence of A. phagocytophilum in I. scapularis ticks increases their ability to survive in the cold. We identified an I. scapularis antifreeze glycoprotein, designated IAFGP, and demonstrated via RNAi knockdown studies the importance of IAFGP for the survival of I. scapularis ticks in a cold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
199
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(204 citation statements)
references
References 72 publications
3
199
2
Order By: Relevance
“…IAFGP, the I. scapularis antifreeze glycoprotein, is induced by ticks in the presence of A. phagocytophilum (26), and silencing iafgp impairs A. phagocytophilum colonization of the gut. Independently, we demonstrated IAFGP to inhibit biofilm formation among Gram-positive pathogens such as S. aureus (25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IAFGP, the I. scapularis antifreeze glycoprotein, is induced by ticks in the presence of A. phagocytophilum (26), and silencing iafgp impairs A. phagocytophilum colonization of the gut. Independently, we demonstrated IAFGP to inhibit biofilm formation among Gram-positive pathogens such as S. aureus (25).…”
Section: Discussionmentioning
confidence: 99%
“…However, unique physical characteristics and previously determined molecular evidence suggest the absence of peptidoglycan from A. phagocytophilum (62)(63)(64), which would nullify any effect IAFGP (or P1) would have on A. phagocytophilum. Our earlier work described the role for elevated levels of IAFGP, upon A. phagocytophilum infection of Ixodes ticks, to protect ticks from the cold environment (26). Therefore, IAFGP aids Anaplasma in two manners: by increasing the ability of ticks to survive in the winter and therefore indirectly increasing the chance of Anaplasma transmission to mice, and by altering the tick microbiomes and their associated biofilms, thereby enhancing its colonization within the tick vector.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting study on I. scapularis showed that A. phagocytophilum promotes cold tolerance through an antifreeze glycoprotein [148]. In the absence of this antifreeze glycoprotein, the survival rate of ticks after exposure to extremely cold temperature and the infection level of A. phagocytophilum following exposure was reduced.…”
Section: Understanding Tick-pathogen Interaction Through Rnaimentioning
confidence: 99%
“…Since then, AFPs have been described in diverse taxa including terrestrial arthropods (Duman, 1977: Duman, 2001Tyshenko et al, 1997;Andorfer and Duman, 2000;Duman et al, 2004;Graham and Davies, 2005;Neelakanta et al, 2010), bacteria and fungi (Duman and Olsen, 1993;Sun et al, 1995;Yamashita et al, 2002;Gilbert et al, 2005) and plants (Griffith et al, 1992;Urrutia et al, 1992;Hon et al, 1994;Duman, 1994;Smallwood et al, 1999;Griffith and Yaish, 2004). Antifreeze proteins lower the non-colligative freezing point of water without depressing the melting point.…”
Section: Introductionmentioning
confidence: 99%